Ekonomi Keluarga TKI dan Pendidikan Anak di Desa Bagik Polak Barat Kecamatan Labuapi Kabupaten Lombok Barat Tahun 2017-2018 - Mastur Mastur (FONDATIA, 2017)
The rapid flow of migrant worker mobility from Lombok to other countries drains almost all villagers of working age. On the one hand, the success of the large number of Overseas Workers contributed to accelerating the growth of income per capita of the villagers, but on the other hand, it continued to accelerate the mobility of the villagers to work abroad despite the high risk route. The departure of a head of a family who becomes a migrant worker abroad will impact on the abandoned family in fulfillment of basic needs that have been fulfilled. The other thing that needs serious attention is the education of the prodigal children who are still in school age. However, a frequent phenomenon, including in Bagik Polak Barat Village, is that the education of children is not getting serious attention, especially the children of migrant workers who are abandoned by their parents abroad. As for the data data collected in this research is the economic level data of migrant workers and junior high school education department. Data completion method used inthis research is done by: Observation, Questionnaire, Documentation and Interview Based on the analysis of the topics discussed in Chapter I and II, it can be drawn a conclusion as follows: 1. Economic income of migrant workers in Bagik Village West Polak Subdistrict Labuapi West Lombok in general is very minimal in accordance with the amount sent by families working abroad. 2. Continuity of education of TKI child in West Bagik Village of Labuapi Subdistrict of West Lombok is varied ie there are only graduated from elementary school. 3. The relationship between the level of income of the families of migrant workers to education in West Bagik Village of Labuapi Subdistrict of West Lombok is at the level of significance of 01% and 05% ie r = 0.654> r-table = 0.279 (05%) and r- count = 0.654 > r-table = 0.361 (1%).